2018
DOI: 10.1038/s41598-017-18618-x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of apple cider vinegar against Escherichia coli, Staphylococcus aureus and Candida albicans; downregulating cytokine and microbial protein expression

Abstract: The global escalation in antibiotic resistance cases means alternative antimicrobials are essential. The aim of this study was to investigate the antimicrobial capacity of apple cider vinegar (ACV) against E. coli, S. aureus and C. albicans. The minimum dilution of ACV required for growth inhibition varied for each microbial species. For C. albicans, a 1/2 ACV had the strongest effect, S. aureus, a 1/25 dilution ACV was required, whereas for E-coli cultures, a 1/50 ACV dilution was required (p < 0.05). Monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 39 publications
5
81
0
Order By: Relevance
“…Apple cider vinegar exerts its antimicrobial activity by limiting the microbial growth and inhibiting mononuclear cytokine and phagocytic activities. Antimicrobial mechanisms of ACV include destroying cell integrity, structural proteins, metabolic enzymes and nuclear compounds (Yagnik, Serafin, & Shah, ). The results of a study revealed that ACV has these antimicrobial properties against Escherichia coli , Staphylococcus aureus and Candida albicans (Yagnik et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apple cider vinegar exerts its antimicrobial activity by limiting the microbial growth and inhibiting mononuclear cytokine and phagocytic activities. Antimicrobial mechanisms of ACV include destroying cell integrity, structural proteins, metabolic enzymes and nuclear compounds (Yagnik, Serafin, & Shah, ). The results of a study revealed that ACV has these antimicrobial properties against Escherichia coli , Staphylococcus aureus and Candida albicans (Yagnik et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial mechanisms of ACV include destroying cell integrity, structural proteins, metabolic enzymes and nuclear compounds (Yagnik, Serafin, & Shah, ). The results of a study revealed that ACV has these antimicrobial properties against Escherichia coli , Staphylococcus aureus and Candida albicans (Yagnik et al, ). In the present study, the skin mucus samples obtained from fish fed with different levels of dietary ACV had antibacterial activity against A. hydrophila and S. iniae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, vinegar supplementation reduced the levels of interleukin-6 (IL-6), an inflammatory cytokine, and the biomarkers nitric oxide (NO) and TNF-α in a clinical study [13][14][15][16]. Recently, vinegars have been reported to reduce body fat and glucose levels, as well as exert anti-oxidant, anti-tumor, and anti-microbial effects [15][16][17][18][19]. The biological activities of fruit vinegars have been studied to exploit the beneficial effects of vinegar.…”
Section: Introductionmentioning
confidence: 99%
“…Apple Cider Vinegar (ACV) is produced from cider that has undergone acetous bioconversion and has relatively low acidity (5% acetic acid). It also contains organic acids, flavonoids, polyphenols, minerals, and vitamins [9]. The present study was undertaken to assess the carriage rate of MRSA among HCWs working at operation rooms (ORs), to evaluate the susceptibility of isolates to mupirocin and Chlorhexidine, and to investigate the antimicrobial activity of different types of vinegars against MRSA isolates to be used as a decolonizing agent.…”
Section: Introductionmentioning
confidence: 99%